Tasting the Future? Cell-Based Meat and the Regulatory Debate in the EU and Beyond (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Cell-based meat is currently at the center of an intense scientific, ethical, political but also legal debate. In fact, the multitude of regulatory approaches disciplining this innovative food highlights the complex balancing between various rights and interests, from consumer health protection to the promotion of technical-scientific development, from environmental sustainability to the guarantee of food security. The paper aims at providing food for thoughts on the topic, presenting the legislative choices promoted both in the EU and outside, with a look at jurisdictions where cell-based meat is already marketed.
Keywords: Cell-based meat; novel foods; food safety; food security; innovation